Complete mitochondrial genome of the Pasiphila chloerata (Lepidoptera: Geometridae) and its phylogenetic implications. Issue 2 (3rd July 2019) - Song, Lu; Shi, Yu-Xia; Li, Jun-Hao; Zhang, Hong-Fei; Ding, Wei-Li; Li, Jin; Yang, Ming-Sheng
Abstract: In this study, the complete mitochondrial genome of Pasiphila chloerata (Mabille) was sequenced and its phylogenetic implications were investigated. The P. chloerata mitogenome is a circular, double-stranded molecule, with 15, 602 bp in length. The typical 37 mitochondrial genes (13 protein-coding genes (PCGs), 22 tRNAs, and 2 rRNAs) and an A + T-rich region are included. Gene content and arrangement are highly conserved and typical of Lepidoptera. Phylogenetic analyses based on the combined 37 mitochondrial genes consistently recovered the Larentiinae and Ennominae involved are reciprocally monophyletic with the highest supports. The P. chloerata was clustered with other two members of the Larentiinae, reinforcing that of previous morphological studies.